Clot Accumulation Characteristics of Plasminogen-bearing Liposomes in a Flow-system - Heeremans, J. L. M.; Prevost, R.; Feitsma, H.; Kluft, C.; Crommelin, D. J. A. (Thrombosis and Haemostasis, 1998)
In this study, the clot accumulation properties of liposome-coupled plasminogen were compared to those of free (non-liposomal) plasminogen in an in vitro, closed-loop, flow-system. After introduction of a clot into the closed system, double-radiolabelled plasminogen-liposomes were administered and the accumulation of radiolabel on the entire clot was measured.Liposomal plasminogen showed improved accumulation over free plasminogen, on both a fibrin clot and a whole blood clot. Moreover, once liposomal plasminogen was fibrin associated, it could not be washed away with buffer, in contrast to free plasminogen. Liposomal plasminogen was able to compete successfully with an excess of free plasminogen. The plateau levels for the accumulated amount of plasminogen depended on the incubated amount of plasminogen and were influenced by partial degradation of the clot. Furthermore, it was shown that a threshold liposomal plasminogen surface-density was needed for optimum clot accumulation.